Multiple Choice Questions (MCQ)-Physical Geography for Advanced Level Students - Ruzaik, Fareena; Rose, Asfin (Sheroni Printers & Publication, 2021)
Physical Geography for Advanced Level Students ISBN: 978-624-97677-3-7 published by Printing & publication: Sheroni Printers & Publication.101A New Boundary Road, Karuverppankeny, Batticaloa.
Multiple Choice Questions (MCQ)-Physical Geography for Advanced Level Students
Multiple Choice Questions (MCQ)-Physical Geography for Advanced Level Students ISBN: 978-624-97677-3-7 published by Printing & publication: Sheroni Printers & Publication.
Keywords: human geography, questions, settlements